1997
DOI: 10.1172/jci119483
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic Ca2+ and protein kinase Calpha couple cellular metabolism to membrane K+ permeability in a human biliary cell line.

Abstract: Cholangiocytes represent an important target of injury during the ischemia and metabolic stress that accompanies liver preservation. Since K ϩ efflux serves to minimize injury during ATP depletion in certain other cell types, the purpose of these studies was to evaluate the effects of ATP depletion on plasma membrane K ϩ permeability of Mz-ChA-1 cells, a model human biliary cell line. Cells were exposed to dinitrophenol (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 36 publications
(41 reference statements)
2
26
0
Order By: Relevance
“…Translocation of PKC-␣ after ischemia has also been observed by others. Wang and coworkers 25 demonstrated that PKC-␣ is responsible for the opening of ion channels with ischemia. Others 26 have found a PKC-␣ translocation in ischemic myocardium and myocardial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Translocation of PKC-␣ after ischemia has also been observed by others. Wang and coworkers 25 demonstrated that PKC-␣ is responsible for the opening of ion channels with ischemia. Others 26 have found a PKC-␣ translocation in ischemic myocardium and myocardial cells.…”
Section: Discussionmentioning
confidence: 99%
“…13,15 In addition, PKC␣ is the principal Ca 2ϩ -sensitive PKC isoform detected by isoform-specific antisera. 4,25 Thus, the channels and signaling pathways involved are likely to reflect those operative in primary cells. Cells were passaged at approximately weekly intervals and maintained at 37°C in 5% CO 2 using HCO 3 -containing Minimal Essential Media (Sigma, St. Louis, MO) supplemented with 2 mmol/L glutamine and 5% fetal calf serum for HTC cells, 15,28 and CMRL-1066 media (GIBCO-BRL, Grand Island, NY) supplemented with 10% heat-inactivated fetal calf serum for Mz-ChA-1 cells.…”
Section: Methodsmentioning
confidence: 99%
“…12,20,21 Protein kinase C (PKC) in particular has been shown to have either positive 22,23 or negative 24 effects on recovery from swelling depending on the cell type under investigation. Previous studies in hepatocyte and biliary cell models indicate that PKC␣ directly modulates Cl Ϫ channel activation during metabolic stress, 4,25 but the role(s) of PKC as a signal regulating liver cell volume have not been assessed. PKC␣ is the principal Ca 2ϩ -sensitive PKC isoform present in liver and biliary cell models, 4,[25][26][27] and intracellular dialysis with recombinant PKC␣ stimulates an increase in membrane ion permeability.…”
mentioning
confidence: 99%
“…Furthermore, mastoparan caused sequestration and a reduction in the activity of Rho, similar to the changes seen during ischemia. Ischemia also stimulates K ϩ channel activity in a variety of nonintestinal tissues (14,22,34,40,41 (21,31). Here we show that chemical hypoxia activates basolateral IK Ca channels in human colonic crypts, while simultaneously increasing the permeability of the colonic epithelium.…”
mentioning
confidence: 52%
“…Metabolic stress has previously been shown to activate different types of K ϩ channel in cholangiocytes and hepatocytes (40,41), vascular cells (22,34), and airway cells (14). However, the magnitude of the effects we observed in human colonic crypt cells (45% and ϳ2-fold increases in IK Ca channel activity and whole cell K ϩ conductance, respectively) were much smaller than those reported previously in human hepatoma and biliary cell lines, in which there were 40-to 70-fold increases in whole cell K ϩ conductance (40,41). On the other hand, we observed more sustained responses to chemical hypoxia in human colonic crypt cells compared with those seen in the cell lines.…”
Section: Discussionmentioning
confidence: 99%